Reply to Comments on the Article “[6]-Shogaol Induced Calcium Signal in Rat Insulinoma Cells” - Rebellato, Paola; Islam, Md. Shahidul (JOP. Journal of the Pancreas, 2014)
No abstract avilable Image: Fresh ginger rhizome